Webster's New World College Dictionary (Wiley Publishing, 2004)
In Russian Language. This 4th edition combines the most up-to-date information about our world to present a completely revised, updated and expanded edition for this age of instant global communication. This authoritative reference now includes 5,000 new entries and the only four-color atlas offered by a dictionary of this size. New words, and new biographical and geographical entries are fully integrated into the single alphabetical listing. Thousands of new uses and meanings have been added to many existing entries. The expanded reference section provides easy access to geographical, historical, and other encyclopedic information. Millions of users worldwide value this unique combination of features, found in no other dictionary: * thousands of examples of current word usage * more than 163,000 entries and over 800 illustrations, biographical photographs, and maps * the official dictionary of the Associated Press.